Lifting functors to Eilenberg-Moore category of monad generated by functor CpCp - Pikhurko, О.B.; Zarichnyi, M.M. (Український математичний журнал, 1992)
The second iteration of the contravariant functor of spaces of continuous functions in the pointwise convergence topology is a functorial part of a monad (triple) on the category of Tikhonov spaces. The problem of lifting functors to the Eilenberg-Moore category of this monad is investigated. Друга ітерація контраваріантного функтора просторів неперервних функцій в топології поточкової збіжності є функторіальною частиною монади (трійки) на категорії тихонов-ських просторів. Досліджується задача підняття функторів на категорію Ейленберга — Мура цієї монади.